To solve for b, we can simplify the equation by combining like terms.
Starting with the left side of the equation:
-6b - 6b - 9 = -12b - 9
Now, we can rewrite the equation:
-12b - 9 = 8b - 9
Next, we want to isolate the variable b on one side of the equation. We can do this by adding 12b to both sides:
-12b + 12b - 9 = 8b + 12b - 9
-9 = 20b - 9
Now, we can simplify the equation further:
-9 = 20b - 9
Finally, we see that the equation simplifies to -9 = -9. This means that the statement is always true, regardless of the value of b. Therefore, the equation has an infinite number of solutions.
-6b–6b–9=8b–9
1 answer